Könyvelő iroda újragondolva a XXI. században - Németh Eszter (2019)
The topic of my thesis is a quite innovative, not really well known type of business and service, based on two essential components. On the one hand, this modern business contains the services of accounting offices, on the other hand the introduction and development of the integrated enterprise management system has supported its emergence, while it has evolved thanks to the rapid advancement of the IT after all. The fusion of them led to the introduction of this innovative service by the executive director. It would also be called a new kind of accounting office, as the title suggests, moved to new foundations in the XXI. century. An in-depth interview with the executive director of the company provided me a lot of information, as far as the integrated enterprise management service is concerned. The market of large companies is full of businesses supplying Enterprise Resource Planning (ERP), so the market of small or medium-sized enterprises seems to be the potential demand for this. The founder of the company took advantage this niche market and set up this innovative business what aims to offer services for companies interested in having more information about their own activity, however introducing an ERP system is not affordable for them. Their purpose is performing everything from the corporate governance to the administration beyond the accounting service, they deal with invoicing, bank transfers, credit applications and financial plans etc., in order to make it possible for the client to concentrate only on the income-generating activity, revenue maximisation and the expansion of products and services. As a result, their partners will be able to win a competitive advantage in today’s fierce economic competition. My central topic is to compare and contrast the services of accounting offices to the activity of a company supplying an integrated enterprise management system. In the first volume I am introducing the growth of the accounting offices, hook-ups, the maintenance of partnerships and their services, than I aimed to map the introduction and development of ERP systems what has served as the basis of the IT background. The fourth volume is dealing with the hook-ups and the maintenance of partnerships in the case of the new activity as well, involving the scope of their services, the positions and the labour process in the company on a daily basis in order to get an overall picture about the enterprise, than this comparison is expounded in details in the next volume. I also paid great attention to introduce the advantages of the integrated enterprise management system over against the service of an accounting office. Aiming to get an insight into the back office activity of micro and small-sized enterprises, who is responsible for particular business and what tools are usually taken, I used a questionnaire survey concentrating on whether there is a demand for the enterprise management service or not. The goal I set was drawing the attention to the outdated tools what are not appropriate to provide up-to-date information.